Eradication Strategy against the Crime of Money Laundering in Indonesia - Fanny Tanuwijaya; Echwan Irianto; I Wayan Yasa; Dodik Prihatin AN; Bhim Prakoso (Budapest International Research and Critics University, 2022)
The crime of money laundering can tarnish the life of the nation and state because this crime can endanger the stability and security of the community. This study aims to examine strategies for eradicating the crime of money laundering. Because the crime of money laundering is an act that is continued or continued from the predicate crime where the person perpetrators process large sums of illegal money proceeds of crime into apparently clean or lawful funds, using sophisticated, creative and complex methods. From the results of the study there are two main things that can be concluded. First, the criminal law policy in criminal law reform in the field of money laundering crime which focuses on policies for formulating criminal acts, criminal liability, and criminal sanctions. formulated in a statutory regulation. Second, criminal law policies in the framework of overcoming the crime of money laundering can be formulated as an effort to make and shape criminal law regulations in the future effectively and efficiently.